Utilization of Polyethylene Terephthalate (PET) Plastic Waste as Material in AC-WC Mixture - Hafidz, Muhammad; Mayuni, Siti; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2025)
Plastic waste is a global environmental issue that also poses significant challenges in Indonesia. As one solution, the utilisation of Polyethene Terephthalate (PET) waste as an additive in asphalt concrete wearing course (AC-WC) mixtures has been developed to enhance the mechanical performance of pavements while reducing environmental impact. This study aims to determine the Optimum Asphalt Content (OAC), analyse the performance of the asphalt mixture, and evaluate its Marshall characteristics. The research was conducted in two stages based on the 2018 Bina Marga specifications (revision 2): the first stage involved determining the OAC without PET (using asphalt content variations of 4,5%